EVALUASI KEBIJAKAN SEKOLAH PENGGERAK DALAM MEWUJUDKAN PROFIL PELAJAR PANCASILA DI SMA NEGERI 1 MENGANTI DAN SMA NEGERI 1 BALONGPANGGANG - Moh. Hudhori; Muhamad Sholeh; Mufarrihul Hazin; Mochamad Nur Salim; Amrozi Khamidi; Kaniati Amalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the implementation of the Sekolah Penggerak policy in realizing the Pancasila Student Profile at SMA Negeri 1 Menganti and SMA Negeri 1 Balongpanggang. The research method used is qualitative research with the CIPP (Context, Input, Process, Product) evaluation model. Data was collected through interviews, observations, and documentation, then analyzed descriptively. The results indicate that in the context aspect, the policy is relevant to the school's vision and mission, but there are challenges in the school's initial readiness. In the input aspect, human resources and infrastructure support implementation but still require optimization. The process evaluation shows that project-based learning methods have been implemented, although there are still obstacles in student engagement and parental support. In the product aspect, the policy has positively contributed to improving student character and academic outcomes, but gaps remain in understanding Pancasila values. Based on these findings, it is recommended to enhance teacher competence, strengthen infrastructure, increase parental involvement, and conduct continuous monitoring and evaluation to ensure that the Sekolah Penggerak policy effectively shapes the Pancasila Student Profile.